Cultivable Microbial Diversity Associated With Cellular Phones - Kurli, Rashmi; Chaudhari, Diptaraj; Pansare, Aabeejjeet N.; Khairnar, Mitesh; Shouche, Yogesh S.; Rahi, Praveen (Frontiers in Microbiology, 2018)
A substantial majority of global population owns cellular phones independently to demographic factors like age, economic status and educational attainment. In this study, we investigated the diversity of microorganisms associated with cellular phones of 27 individuals using cultivation-based methods. Cellular phones were sampled using cotton swabs and a total of 554 isolates representing different morphotypes were obtained on four growth media. Matrix-assisted laser desorption ionization time of flight (MALDI-TOF) mass spectrometry could generate protein profiles for 527 isolates and species-level identification was obtained for 415 isolates. A dendrogram was constructed based on the protein profiles of the remaining isolates, to group 112 isolates under 39 different proteotypes. The representative strains of each group were selected for 16S rRNA gene and ITS region sequencing based identification. Staphylococcus, Bacillus, Micrococcus and Pseudomonas were the most frequently encountered bacteria, and Candida, Aspergillus, Aureobasidium and Cryptococcus were in case of fungi. At species-level the prevalence of Micrococcus luteus, Staphylococcus hominis, Staphylococcus epidermidis, Staphylococcus arlettae, Bacillus subtilis and Candida parapsilosis was observed, most of these species are commensal microorganisms of human skin. UPGMA dendrogram and PCoA biplot generated based on the microbial communities associated with all cellular phones exhibited build-up of specific communities on cellular phones and the prevalence of objectionable microorganisms in some of the cellular phones can be attributed to the poor hygiene and sanitary practices. The study also revealed the impact of MALDI-TOF MS spectral quality on the identification results. Overall MALDI-TOF appears a powerful tool for routine microbial identification and de-replication of microorganisms. Quality filtering of MALDI-TOF MS spectrum, development of better sample processing methods and enriching the spectral database will improve the role of MALDI-TOF MS in microbial identifications.